Psychoeducation of preventive action against bullying behavior in MIN 1 Blitar - Istiqomah, I.; Hidayati, Diana Savitri (Universitas Muhammadiyah Malang, 2020)
Bullying in schools is one or a factor that becomes a problem / obstacle in achieving the Sustainable Development Goals (SDGs), so that campaigns and enlightenment to the public about the various impacts and efforts to overcome bullying must be encouraged. In this regard, this article aims to describe the preventive action psychoeducation service activities against bullying behavior at MIN 1 Blitar. Community service participants are Teachers and Parents of Students of MIN 1 Blitar. The target of this community service is that teachers and parents at MIN 1 Blitar are able to understand the condition of students or their children so that they are not prone to becoming victims of bullying or becoming perpetrators of bullying, creating a Peaceful school. The method used is to provide a scale of Bullying, psychoeducation and focus group discussion (FGD) to teachers and parents of students of MIN 1 Blitar. Based on the post-test results of the fifth-grade students of MIN 1 Blitar, it is known that 6.5% were identified as bullying perpetrators while 15% were identified as victims of bullying. This service activity is carried out in several forms, namely psychoeducation, FGD and self-help groups, which are preventive measures of psychoeducation against bullying behavior.